2018
DOI: 10.1111/acps.12911
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of depressive and bipolar disorder patients with mixed features

Abstract: ObjectiveTo assess differences between subjects with vs. without mixed features in major affective disorders.MethodsIn 3099 out‐patient subjects with DSM‐5 major depressive disorder (MDD, n = 1921) or bipolar disorders (BD, n = 1178), we compared those with (Mx) vs. without (Non‐Mx) mixed features (agitated‐irritable depression or dysphoric [hypo]mania) in an index episode.ResultsPrevalence of Mx averaged 21.9% [CI: 20.5–23.4] overall, ranking: BD‐II > BD‐I > MDD, and in BD depression ≥ [hypo]mania > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 36 publications
6
40
2
3
Order By: Relevance
“…48 A potential limitation of our study is the conceptualization of the term agitated depression. There is not a unanimous definition of AD in the literature to date 1,20 with concurrent manic symptoms in the absence of motor agitation. 34 We did not have data on other specific manic/hypomanic symptoms concurrent with the depressive episode, and thus could not extend our definition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…48 A potential limitation of our study is the conceptualization of the term agitated depression. There is not a unanimous definition of AD in the literature to date 1,20 with concurrent manic symptoms in the absence of motor agitation. 34 We did not have data on other specific manic/hypomanic symptoms concurrent with the depressive episode, and thus could not extend our definition.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that individuals with bipolar disorder who experience mixed states have a more severe illness course with high risk of suicide. 20,28 Rihmer et al 25 reported a high prevalence of depressive mixed states among suicide attempters, and in particular psychomotor agitation is known to be a significant risk factor for suicide. 26 Consistent with previous research, we found an association between AD and lifetime suicide attempt.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations